Microbiological and parasitological quality of “Panga fish" (Pangasius spp.) - Resplandes, E. E. V.; Socoloski, S. N. G.; Kemper, R. T.; Moreira, P. S. A.; Anjos, T. R.; Fortuna, J. L. F.; Vieira, T. B. (Scientific Electronic Archives, 2017)
The goals of the study were to verify the presence of coliforms in frozen Basa fish fillets market in different cities in Mato Grosso State, Brazil and identify if they complied with the standards established by the Brazilian Food Legislation. Twenty-five samples were collected at supermarkets in eight cities in Mato Grosso State. The microbiological analyses were performed using the coagulase-positive Staphylococci count; screening for Salmonella sp., enumeration of total coliforms, thermotolerant and Escherichia coli. In addition, it proceeded to parasitological analysis by parasitic morphological structures identification. Â Coagulase-positive Staphylococci strains were isolated in two samples (8%) with 3,8 x 10 4 Â and 1,4 x 10 5 CFU/g. In one sample (4%), the values obtained were 23 MPN/ g for total coliforms count, 4 MPN/ g for thermotolerant coliforms and 4 MPN/ g for E. coli. Salmonella spp. strains were not isolated. Parasitic structures were not observed. Frozen Panga fish fillets demonstrated low levels of coliform contamination; indicating that it is safe for human consumption considering that 23 (92%) of the analyzed samples were within the standards established by the current Brazilian Food Legislation.